Automatic washroom light with LCD display / Muhammad Faizwan Abu Aziz & Muhammad Shahiran Roslanor - Muhammad Faizwan, Abu Aziz; Muhammad Shahiran, Roslanor (2015)
The Automatic Washroom Light with LCD Display is a device that consists of one microcontroller. The washroom light will be connected to LCD display circuit. An automatic washroom light will be operated when the door is closed. The lamp will remain on until the switch detects the door open. The switch that we using to detect the movement of the door is Micro Switch. The circuit will design around the popular PIC it is PIC16F877A. This project will be use the PROTEUS 8.0 to design the layout and run the simulation.